Volatile profile of the headspace fraction of "assa-peixe" (Vernonia sp.) honeys - Ribeiro,Mariana Carvalho (2008)
The volatile compounds were isolated from the headspace fraction of "assa-peixe" honeys by adsorptive column chromatography, eluted with acetone and analysed by GC-FID and GC-MS. Volatile compounds were separated using a polar phase column. Low- and medium-boiling point volatile compounds predominated in the headspace. A large proportion of 3-penten-2-one (80.5 ± 13.9 µg.kg-1) and benzaldehyde (25.9 ± 4.2 µg.kg-1) was found in the headspace fraction, while 2-penten-1-ol, 3-hexenyl butanoate, octadecane and hexanoic acid (<0.01 µg.kg-1) were by far the less abundant volatile compounds. A total of 12 volatile compounds were identified and, among them, 5 compounds were reported as "assa-peixe" honey constituents for the first time. Of the 5 new volatile compounds reported, 3-penten-2-one, dodecane, tridecane and benzaldehyde were definitively identified in the headspace fraction of Brazilian "assa-peixe" honeys.